GROWTH RESPONSE OF BANJAR SIAM ORANGE (CITRUS NOBILIS LOUR VAR. MICROCARPA HASSK) SEEDS TO FERTILIZER OF GOAT MANURE AND NPK IN RED YELLOW PODSOLIC SOIL - Ilham B.W.; Titin A.A.; Syahrudin; Siti Z.; Abdul S.; Kambang V.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Siam Banjar oranges are a type of fruit that is widely cultivated in Kalimantan. Limited quality seeds are one of the obstacles in its cultivation. The purpose of this study was to study the effect of applying goat manure and NPK fertilizer on the growth of Siam Banjar orange grafting seedlings on PMK soil. The research design used a factorial Completely Randomized Design (CRD) repeated 3 times. The first factor was the administration of goat manure (control; 100; 200 and 300 g/polybag). Meanwhile the second factor was NPK fertilization (control; 2.5 and 5 g/L). The results showed that there was an interaction between the addition of 100 g/polybag goat manure and 2.5 g/L NPK on stem diameter (7.1 mm). The addition of 100 g/polybag goat manure was able to increase shoot length (29.22 cm), number of leaves (21.11 strands), leaf area (258.61 cm2). NPK administration at a dose of 5 g/L increased shoot length (37.33 cm), number of leaves (26.66), and leaf area (353.19 cm2). A combination of 100 g/polybag goat manure and NPK dose of 5 g/L can be applied to increase the growth of Siam Banjar orange grafting seedlings.